Anabolic steroids abuse-induced cardiomyopathy and ischaemic stroke in a young male patient. (26th February 2014) - Shamloul, Reham Mohammed; Aborayah, Ahmed Fathy; Hashad, Assem; Abd-Allah, Foad
Abstract : We report a case of a 37-year-old man presented with acute stroke and hepatorenal impairment which were associated with anabolic-androgenic steroids (AAS) abuse over 2 years. Despite the absence of apparent symptoms and signs of congestive heart failure at presentation, an AAS-induced dilated cardiomyopathy with multiple thrombi in the left ventricle was attributed to be the underlying cause of his condition. Awareness of the complications of AAS led to the prompt treatment of the initially unrecognised dilated cardiomyopathy, and improved the liver and kidney functions. However, the patient was exposed to a second severe ischaemic event, which led to his death. This unique and complex presentation of AAS complications opens for better recognition and treatment of their potentially fatal effects.